2019
DOI: 10.1111/mpp.12852
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy–virus interplay in plants: from antiviral recognition to proviral manipulation

Abstract: Summary Autophagy is a conserved self‐cleaning and renewal system required for cellular homeostasis and stress tolerance. Autophagic processes are also implicated in the response to ‘non‐self’ such as viral pathogens, yet the functions and mechanisms of autophagy during plant virus infection have only recently started to be revealed. Compelling evidence now indicates that autophagy is an integral part of antiviral immunity in plants. It can promote the hypersensitive cell death response upon incompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 58 publications
0
49
0
Order By: Relevance
“…Autophagy is known to play an antiviral role in plant [ 29 ]. To further investigate the effect of autophagy on PMMoV infection, we silenced NbATG3 , NbATG5 , NbBeclin1 , NbATG7 and NbATG8a expressions in N. benthamiana plants individually using specific TRV-based VIGS vectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is known to play an antiviral role in plant [ 29 ]. To further investigate the effect of autophagy on PMMoV infection, we silenced NbATG3 , NbATG5 , NbBeclin1 , NbATG7 and NbATG8a expressions in N. benthamiana plants individually using specific TRV-based VIGS vectors.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies on plant autophagy and pathogen infections have revealed the importance of autophagy during pathogen infections [ 29 , 46 ]. Other studies have shown the specific roles of autophagy in eliminating viruses in mammalian cells [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it has been shown that both host proteins rgs-CaM, a calmodulin-like protein, and NBR1, an autophagy cargo receptor, can mediate the degradation of HC-Pro via autophagy to restrict virus infection [96,98]. Moreover, like many animal viruses, potyviruses have evolved some strategies to subvert autophagy to promote their infection [99]. For instance, suppressor of gene silencing 3 (SGS3) and its intimate partner RNA-dependent RNA polymerase 6 (RDR6) are two crucial components of RNA silencing.…”
Section: Nib and Autophagymentioning
confidence: 99%
“…Autophagy is a targeted degradation and recycling pathway in plants activated under nutritional deprivation, but its network of autophagosomes can also perform the targeted removal of unwanted cellular components. In several cases, viruses interfere with and suppress host autophagy because it is targeting viral factors for degradation and thus hindering infection (Kushwaha et al, 2019). In other cases, pathogens have evolved to hijack autophagy to degrade host defense components, such as the RNA silencing pathway, for their own benefit (Kushwaha et al, 2019).…”
mentioning
confidence: 99%
“…In several cases, viruses interfere with and suppress host autophagy because it is targeting viral factors for degradation and thus hindering infection (Kushwaha et al, 2019). In other cases, pathogens have evolved to hijack autophagy to degrade host defense components, such as the RNA silencing pathway, for their own benefit (Kushwaha et al, 2019). However, the Cotton leaf curl Multan virus (CLCuMuV) investigated by researchers in the lab of Yule Liu, induces autophagy in the host Nicotiana benthamiana that in turn targets a key viral protein, βC1, for degradation (Haxim et al, 2017).…”
mentioning
confidence: 99%